ADAPTIVE LEARNING DALAM DESAIN INSTRUKSIONAL: PENDEKATAN STRATEGIS MENINGKATKAN KETERLIBATAN MAHASISWA DI E-LEARNING PERGURUAN TINGGI - Rani; Jihan; Adyanata Lubis; Agung Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the integration of adaptive learning in instructional design and its impact on student engagement in the context of online learning in higher education. Using a systematic literature review approach, this study analyzes ten scientific articles through thematic analysis and source triangulation methods to obtain credible and comprehensive findings. The results of the analysis reveal that adaptive learning supports the personalization of the learning process through the use of learning analytics, learning style mapping, and adaptive content arrangement. Adaptive instructional design serves as an implementation framework that allows for learning flexibility through formative assessment, scaffolding, and material modularization. The integration of the two components has a positive impact on student engagement, both in the affective, cognitive, and behavioral dimensions. This study produces a conceptual model that explains the logical relationship between adaptive learning, instructional design, and student engagement. The implications of these findings encourage the development of a more personalized e-learning system and learning that is oriented to individual student needs.